Honourable Slaves? The Socio-Economic Aspects of Enslaved Wet-Nurses in Classical Athens - Hansen, Emil Theodor (Culture and History: Student Research Papers, 2025)
In the huge collection of ancient Greek grave steles we find a number of inscriptions dedicated to wet nurses of the rich, elite citizenry of Classical Athens. This is a quite peculiar and noteworthy appearance, both keeping in mind that these wet nurses are enslaved people, and therefore ‘socially dead’, as well as being females in ancient Athens – a situation without any form of political, legal or social rights. This article sets out to explore why these honours came to be, and what they essentially means for the wet nurses in question, in terms of social status and socioeconomic opportunities. Throughout, it will be argued that these nurses display a dichotomous position in the ancient Greek household, due to their privileged and problematic knowledge of the most intimate aspects of the citizen’s private life.